A therapy parameter-based model for predicting blood glucose concentrations in patients with type 1 diabetes. Issue 2 (February 2015) - Bock, Alain; François, Grégory; Gillet, Denis
<x xml:space="preserve">Abstract</x> Highlights New glucose prediction model for the treatment of type 1 diabetes. Strongly correlation of model parameters with therapy parameters. Equivalent predictions to models with 50% more parameters. Validation on clinical data as well as UVa simulation data.